2013
DOI: 10.1002/pip.2336
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the influence of an embedded porous silicon layer on the bulk lifetime of epitaxial layers and the interface recombination at the epitaxial layer/porous silicon interface

Abstract: Porous silicon plays an important role in the concept of wafer-equivalent epitaxial thin-film solar cells. Although porous silicon is beneficial in terms of long-wavelength optical confinement and gettering of metals, it could adversely affect the quality of the epitaxial silicon layer grown on top of it by introducing additional crystal defects such as stacking faults and dislocations. Furthermore, the epitaxial layer/porous silicon interface is highly recombinative because it has a large internal surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Nanostructuring of silicon leads to unique properties, different from the bulk material, such as light emission in the visible range [16][17][18], high surface area [19,20], tunable morphology [21,22], and biocompatibility [23], to name a few. Due to the porous structure it is distinguished as a template for the incorporation of various materials [24][25][26]. Molecules can be attached size-selectively due to different pore diameters [20,27], which allows the use of the system as a sensor, where the detection is mainly performed by determining the reflective index [28].…”
Section: Silicon Templatesmentioning
confidence: 99%
“…Nanostructuring of silicon leads to unique properties, different from the bulk material, such as light emission in the visible range [16][17][18], high surface area [19,20], tunable morphology [21,22], and biocompatibility [23], to name a few. Due to the porous structure it is distinguished as a template for the incorporation of various materials [24][25][26]. Molecules can be attached size-selectively due to different pore diameters [20,27], which allows the use of the system as a sensor, where the detection is mainly performed by determining the reflective index [28].…”
Section: Silicon Templatesmentioning
confidence: 99%
“…Structural defects are one possibility and are believed to originate in single-crystal epi wafers from incomplete pore closure during porous silicon annealing. 15,46 Stacking faults and dislocations are revealed in portions of Gen I (1 cm 2 ) and Gen II (4 cm 2 ) samples after gettering 47 and analyzed with an optical microscope and counting software. 48 The wafer surface area covered by regions of high (>10 5 cm…”
mentioning
confidence: 99%
“…High defect density may play a role in breakage and shunts. Recently, it has been shown that porosity can be completely extracted from the epi-layer if high quality material and engineered macropores with large aspect ratios are used [135]. It turns out an epi-layer is not even needed since the carefully engineered macropores can be manipulated to exfoliate a high quality thin wafer from the thick substrate [136][137][138].…”
Section: Epitaxial (Epi) Growth Processesmentioning
confidence: 99%